Poetics of the stranger: Dilemmas of the self and the stranger as poetic reflections pointing to an anthropological perspective - Cawasjee, Shyam (Psyke & Logos, 2023)
The primary aim of this paper is to develop a concept of the stranger in relation to those dilemmas of the self which communicate themselves in the language of poetics. This framework leads us to such experiences as »being strangers to ourselves« or what might also be described as »finding the stranger in ourselves«. in a sense these experiences are also significantly associated with the concept of authenticity as we have come to know it from the works of such authors as D.H. Lawrence and Joseph Conrad. All this points to the faet that in the present context the concept of the stranger occupies a key position which comes to light in relation to such themes as the dilemmas of the self, the nature of authenticity and the inherently poetical form in which they often come to expression.